Ecuador Potato Middlemen Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
Ecuador potato middlemen survey is the study of the middlemen in the potatoes value chain in Ecuador. These data allow quantifying the extent of food loss at the middlemen level using consistent approaches that are comparable across commodities and regions. They also enable characterizing the nature of food loss, specifically the production stages and the particular processes at which loss is incurred.